An Analysis of Hemingway’s Symbolism in the Snow of Kilimanjaro - Li , Peiyan (Journal of Theory and Practice of Social Science, 2023)
This paper analyzes the symbolic meaning of Hemingway’s well-known short story The Snow of Kilimanjaro based on symbolism theory, which makes readers better understand the Hemingway’s powerful creation of character and his unique language style. This paper analyzes the images of snowy mountains, snow in memory, leopards, wine, gangrene and their relations with Harry, and explains their symbolic meanings in the novel. Although images such as wine and gangrene imply that Harry's death is too heavy, the snow mountain of Kilimanjaro and the leopard symbolize Harry's spiritual immortality.